CD95-induced JNK activation signals are transmitted by the death-inducing signaling complex (DISC), but not by Daxx - Hofmann, Thomas G.; Dröge, Wulf (International journal of cancer, 2001)
Here we investigated CD95-mediated JNK activation pathways and their physiological relevance by employing a variety of cell lines with deficiencies in individual signal transmitting proteins. JNK activation was completely dependent on the activation of caspases in type I and type II cells, as revealed by the inhibitory effects of the caspase inhibitors zVAD-fmk or the cowpoxvirus-encoded CrmA protein. Jurkat cells deficient in caspase-8 or expressing a dominant negative (DN) form of FADD were unable to induce JNK in response to CD95 ligation, indicating that these death-inducing signaling complex (DISC) proteins are required for signal transmission. Activation of caspases, JNK and apoptosis occurred with a markedly slower kinetics in cells expressing a DN version of ASK1, revealing an important contribution of ASK1 for these processes. A C-terminally truncated version of Daxx impaired CD95-mediated apoptosis without affecting the JNK signal. DN forms of FADD, MKK4 and MKK7 completely inhibited CD95-mediated JNK activation but remained without impact on cell killing, indicating that JNK activation is not required for the execution process of CD95-mediated cell killing.
Gesehen am 03.02.2021